The prevalence of alcohol use among medical students in Poland - Woźniakowski, Mateuz; Zarobkiewicz, Michał; Sławiński, Mirosław; Świerszcz, Łukasz; Roszkowska, Anna; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2017)
Introduction. Alcohol is the most widely used drug worldwide. Medical students should be aware of its possible harmful properties although they are known to consume large amounts of alcohol. Therefore analysis of their drinking patterns is important for public health. Aim of the study. Analysis of alcohol consumption patterns among Polish medical universities students. Material and methods. Students of different Polish medical universities were asked to fill a self-prepared survey on alcohol consumption. 852 fulfilled questionnaires were gathered. The statistical analysis was performed with Statistica 13 (Statsoft, USA). Results. 99.19% of students (N=860) have declared trying alcohol. 35,35% (N=304) of respondents declared the age of first alcohol consumption as between 15 and 18 years. 31,28% (N=269) of respondents admitted drinking once a week, (27,33%, N=235) twice a week. Beer was pointed as the most frequently consumed alcohol – (51,28%, N=441). 241 students (28,02%) admitted participating in classes under the influence of alcohol. Conclusions. Study reveals some risky alcohol drinking behavior, for example attending classes under the influence of alcohol. During classes they often have contact with patients therefore it can be really dangerous tendency.